Efektivitas Legislasi BPD dalam Pembentukan Peraturan Desa: Studi Kasus Kecamatan Batudaa dalam Kerangka Administrasi Publik - Yurifto Sastro; Rusli Isa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of the legislative function of the Village Consultative Body (BPD) in the formation of village regulations in Batudaa Subdistrict, Gorontalo Regency. The BPD’s legislative function is an important part of democratic and participatory village governance. Within the framework of public administration, legislative effectiveness is measured not only by regulatory outputs but also by participatory processes, transparency, and institutional accountability. This study recommends strengthening the BPD’s capacity through legislative training, enhancing public participation mechanisms, and improving coordination among village actors as strategic steps to increase the effectiveness of village legislation. These findings are expected to contribute to the development of more responsive and accountable village governance in the context of public administration.